A Implementation of Contextual Approach to Improve Motivation and Student Learning Outcomes in Class VI Learning Science Learning SD Negeri 24 Ganting Singgalang - Hilda Marta; Yanti Fitria; Hadiyanto Hadiyanto; Risda Amini (International Journal of Educational Dynamics, 2019)
This study aims to describe the Application of Contextual Approaches to Improve Student Learning Outcomes and Motivation in Class VI Learning in Class VI of Singgalang Elementary School 24. This research is a class action research, which is a study developed jointly for researchers and decision makers about variables that are manipulated and can be used to make improvements. Repairs are carried out with two cycles, namely cycle I and cycle II. Data from research results can be grouped into two, namely quantitative and qualitative data. Quantitative data, namely numerical data, are qualitative data in the form of descriptive. As the subjects in this study were teachers and students of class VI SDN 24 Ganting Singgalang District X Koto Tanah Datar District, amounting to 27. The results of the study obtained an average value of students in cycle I was 64.3 experienced an increase in the second cycle, 96. Thus, increased by 31%. While the affective aspects obtained an average score of 96 and the psychomotor aspects obtained an average score of 94. Thus, students' learning motivation with the application of a contextual approach in class VI of Singgalang Elementary School 24 Ganting was stated to have increased.